Laparoscopic Reversal of Hartmann’s Procedure: State of the Art 20 Years after the First Reported Case - Adriana Toro; Annalisa Ardiri; Maurizio Mannino; Antonio Politi; Andrea Di Stefano; Zia Aftab; Abdelrahman Abdelaal; Maria Concetta Arcerito; Andrea Cavallaro; Marco Cavallaro; Gaetano Bertino; Isidoro Di Carlo (Gastroenterology Research and Practice)
Introduction. Aim of the present work is to review the literature to point out the role of laparoscopic reversal of Hartmann procedure. Material and Methods. Number of patients, age, sex, etiology, Hinchey classification, interval between procedure and reversal, position of the first trocars, mean operative time (min), number and causes of conversion, length of stay, mortality, complications, and quality of life were considered. Results. 238 males (52.4%) and 216 females (47.6%) between 38 and 67 years were analyzed. The etiology was diverticulitis in 292 patients (72.1%), carcinoma in 43 patients (10.6%), and other in 70 patients (17.3%). Only 7 articles (22.6%) reported Hinchey classification. The interval between initial procedure and reversal was between 50 and 330 days. The initial trocar was open positioned in 182 patients (43.2%) through umbilical incision, in 177 patients (41.9%) in right upper quadrant, and in 63 patients (14.9%) in colostomy site. The operative time was between 69 and 285 minutes. A total of 83 patients (12.1%) were converted and the causes were reported in 67.4%. The length of stay was between 3 and 12 days. 5 patients (0.7%) died. The complications concern 112 cases (16.4%). Conclusion. The laparoscopic Hartmann’s reversal is safer and achieves faster positive results.